(Nsw~(B-(NRADIOMETRIQ WODNOJ POWERHNOSTI I PO^WOGRUNTOW (B/s - (N{UTKO(B, (NaNATOLIJ mIHAJLOWI^s; (NaRMAND(B, (Nn(B.(Na(B.s ((NmOSKWA (B:s (NnAUKA(B,s, 1986)
(NbIBLIOGR(B.: (NS(B. 174-186 (338 (NNAZW(B.)s
(Nan sssr(B, (NiN(B-(NT RADIOTEHNIKI I \LEKTRONs
Keywords: (NrADIOMETRI^ESKIJ METODs; (NfIZIKO(B-(NGEOGRAFI^ESKIE ISSLEDOWANIQs